Application and prospect of image registration technology in the diagnosis and treatment of temporomandibular joint disorders - XIE Yuting, TANG Wen, WU Yue, CAO Libo, MA Jiajun, IZADIKHAH Iman, CHEN Yan, CAO Dan, YAN Bin, ZHU Linlin, XIE Lizhe (Kouqiang yixue)
With advancements in radiology, endoscopic techniques, surgical treatments, cell biology and molecular biology, the understanding of temporomandibular disorders(TMD)has increased. The temporomandibular joint (TMJ) is a complex structure comprising both soft and hard tissues. Within the TMJ, the temporomandibular disc is a soft tissue structure that connects the mandible to the skull, providing cushioning and stability during joint movement. Different imaging techniques have their own advantages and limitations in the diagnosis and treatment of TMD. Therefore, using image registration technology to assess the condition and position of the articular disc provides new research perspectives for evaluating TMD, which may contribute to the diagnosis and treatment. This article reviews the latest advancements in TMJ imaging, explores the applications of various image registration techniques, particularly in the context of TMD diagnosis and treatment, and discusses future prospects. Combining the research results of some scholars at home and abroad with the author’s clinical experience, the article aims to provide valuable insights for clinicians.